Citric acid is more effective than sodium thiosulfate in chelating calcium in a dissolution model of calcinosis - Kyle A. Burgess; Richard E. P. Winpenny; Alberto Saiani; Aline F. Miller; Ariane L. Herrick; Rachel E. B. Watson (Scientific Reports)
Abstract Calcinosis cutis affects 20–40% of patients with systemic sclerosis. This study tests the hypothesis that calcium-chelating polycarboxylic acids can induce calcium dissolution without skin toxicity or irritancy. We compared citric acid (CA) and ethylenediaminetetraacetic acid (EDTA) to sodium thiosulfate (STS) for their ability to chelate calcium in vitro using a pharmaceutical dissolution model of calcinosis (hydroxyapatite (HAp) tablet), prior to evaluation of toxicity and irritancy in 2D in vitro skin models. Resultant data was used to predict therapeutic concentrations for application in a validated 3D skin irritation model (SkinEthic™; EpiSkin SA) and to assay maximal percutaneous absorption. Dissolution performance was further assessed via ability to dissolve a calcified matrix laid down in vitro. Pharmacological dissolution studies identified that polycarboxylic acids were superior to STS in dissolving HAp tablets. In vitro, compounds had little effect on cell numbers at concentrations of < 10 mM. When applied topically to 3D models as near-saturated solutions, chelators were not irritant nor did they impact model structure histologically. CA was the most efficient chelator of calcium salts. This study highlights polycarboxylic acids, particularly CA, as potential therapies to target calcinosis cutis: these should now be investigated in human studies.